2019
DOI: 10.7759/cureus.4807
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Randomized Pair Comparison of a Barrier Film vs. Standard Skin Care in Preventing Radiation Dermatitis in Post-lumpectomy Patients with Breast Cancer Receiving Adjuvant Radiation Therapy

Abstract: Introduction Patients undergoing adjuvant radiotherapy to the breast often experience radiation dermatitis ranging from mild erythema to moist desquamation. In post-lumpectomy patients, the axilla and inframammary fold are at an increased risk for friction dermatitis. Dermatitis can impact patients’ quality-of-life and may require treatment break/cessation. Our objectives are to assess the efficacy of 3M Cavilon Barrier Film (BF) in preventing and/or delaying the onset of grade-two dermatitis and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…StrataXRT® or alternative product) have also been used in patients undergoing radiotherapy for head and neck cancer, lung cancer and cancer. 25,26 In the study by Chan et al, 25 at the end of treatment grade 2 skin reactions were identified in 80% of patients in the StrataXRT® arm and grade 3 in 28%, compared with 91% and 45% respectively in the control arm. After controlling for the cancer drug cetuximab, the Stra-taXRT® arm had a 12% lower risk of experiencing grade 2 skin toxicity (RRR ¼ 0.876, 95% CI 0.778e0.987) and a 36% lower risk of developing a grade 3 reaction (RRR ¼ 0.648, 95% CI 0.442e0.947).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…StrataXRT® or alternative product) have also been used in patients undergoing radiotherapy for head and neck cancer, lung cancer and cancer. 25,26 In the study by Chan et al, 25 at the end of treatment grade 2 skin reactions were identified in 80% of patients in the StrataXRT® arm and grade 3 in 28%, compared with 91% and 45% respectively in the control arm. After controlling for the cancer drug cetuximab, the Stra-taXRT® arm had a 12% lower risk of experiencing grade 2 skin toxicity (RRR ¼ 0.876, 95% CI 0.778e0.987) and a 36% lower risk of developing a grade 3 reaction (RRR ¼ 0.648, 95% CI 0.442e0.947).…”
Section: Discussionmentioning
confidence: 99%
“…Creams used as control comparators could potentially have influenced the results of these studies. In the study by Lam et al, 26 patients with breast cancer in the sample were treated with either a conventional fractionation (50Gy in 25 fractions) or a hypofractionated biologically equivalent dose.…”
Section: Discussionmentioning
confidence: 99%
“…Radiodermatitis, an inflammatory skin disease, is one of the most common complications of radiotherapy in patients with breast cancer, head and neck cancer, as well as vulvar carcinoma. 8,9 Vulvar carcinoma is a malignant tumor of the female perineum, accounting for about 3% ~5% of female malignant tumors. It mainly occurs in postmenopausal women and tends to increase with age.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of them demonstrated the superiority of this dressing over sorbolene cream in reducing the rates of moist desquamation and pruritus [43]. Two newer randomized controlled trials did not confirm these findings [44,45].…”
Section: Gel Dressingsmentioning
confidence: 94%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/pharmaceutics14061204/s1, Table S1: Proposed T.I.M.E. wound bed preparation for acute and chronic radiation dermatitis, Table S2: Dressings for prevention and treatment of acute radiation dermatitis [19][20][21][22][23][24][25][26][27][28][29][30][31][33][34][35][36][37][38][39][40][42][43][44][45][47][48][49][50][52][53][54][55][56]74].…”
Section: Supplementary Materialsmentioning
confidence: 99%